The Influence of Parenting on Learning Motivation through Emotional Intelligence and Self-Regulation of SMP N 6 Madiun Students - Mahanani Wilujeng; Erwin Erlangga; Rini Sugiarti (Edumaspul: Jurnal Pendidikan, 2024)
The influence of parenting from parents on learning motivation is important to do. However, parenting activities through emotional intelligence and self-regulation of learning motivation are rarely used by researchers. This study aims to determine how influential parenting style is on learning motivation, to find out how influential the strengthening of emotional intelligence and self-regulation in parenting on learning motivation. The subjects of this study amounted to 230 respondents from SMP Negeri 6 Madiun. Data collection is carried out by distributing questionnaires related to parenting, motivation, emotional intelligence, and self-regulation. His data analysis technique uses validity and reliability tests as well as t tests and f tests, and determination coefficient tests. The results of his research are emotional intelligence and self-regulation strengthen parenting on learning motivation. There is a positive relationship and significant influence between parenting through emotional intelligence and self-regulation of learning motivation.